A method for uniformly regulating and preparing a blended film of two-dimensional material-organic silicon

By uniform regulation of the silicone film and two-dimensional material intercalation treatment, a two-dimensional material-silicon blended film was formed, which solved the problem of insufficient pore size screening effect in acetic acid/water separation, and significantly improved the separation factor and water flux.

CN115738764BActive Publication Date: 2025-04-25CHANGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211594692.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-13
Publication Date
2025-04-25
Estimated Expiration
2042-12-13

AI Technical Summary

Technical Problem

In the permeability and vaporization separation of acetic acid/water, the pore size screening effect is weak, resulting in a low separation factor and low mechanical strength of two-dimensional materials and limited performance.

Method used

The silicone sol and the two-dimensional sheet sol solution are preferentially filtered through the microfilter membrane of two pores to improve their uniformity, and the two-dimensional material is inserted into the silicone sol by ultrasonic to form a two-dimensional material-silicon blended membrane, which uses hydrophilic groups of the two-dimensional material to improve separation performance.

Benefits of technology

Effectively reduce the pore size of the silicon network, improve the separation factor and water permeability of the acetic acid/water solution, and enhance the hydrophilicity and water selectivity of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115738764B_ABST
    Figure CN115738764B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a blended membrane by uniformly regulating a two-dimensional material-organosilicon, and belongs to the field of membrane separation technology. The present invention dissolves an organic alkoxysilane precursor in a solvent, and then adds a catalyst and water to form a stable organic silicon sol; a hydrophilic two-dimensional sheet material with acid and alkali resistance and thermal stability is dispersed in a solvent to form a colloidal solution; the organic silicon sol and the two-dimensional sol liquid are filtered through a microfiltration membrane to form a suspension and a sol with uniform particle size, and then ultrasonically mixed together; the mixed sol is further diluted with a solvent, coated on a porous carrier and calcined to obtain an organic silicon blended membrane containing a two-dimensional material. Through the uniformity regulation of the two-dimensional sheet structure and the organic silicon sol, the hybrid silicon membrane exhibits a higher acetic acid / water separation performance in the pervaporation separation of acetic acid / water solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of membrane separation, and specifically relates to a method for preparing a membrane by uniformly regulating and blending a two-dimensional material-organic silicon. Background Art

[0002] Acetic acid is one of the most important chemicals in the chemical industry. It can produce a large amount of chemicals and has a huge annual global demand. In the preparation and application of acetic acid, it is mostly miscible with water and needs to be further purified to reach the maximum concentration of acetic acid. Acetic acid and water are near-boiling point mixtures. Traditional separation methods, such as distillation, consume huge amounts of energy during the separation process and are accompanied by a large amount of pollution. Pervaporation in membrane separation technology has the advantages of energy saving and cost saving, and has broad application prospects in the dehydration and separation of organic water mixtures.

[0003] In order to be used in pervaporation dehydration under acidic conditions, the membrane material should have excellent acid resistance and hydrothermal stability. Organic silicon membranes are prepared by using alkoxysilanes containing organic groups instead of ethyl orthosilicate. The organic groups contained in them overcome the poor stability of Si-O-Si bonds in inorganic silicon dioxide membranes under hydrothermal conditions and have excellent acid resistance (Journal of Membrane Science 324 (2008) 111–118). However, compared with inorganic SiO2 membranes, the organic groups in the organosilicon membrane act as bridges, increasing the pore size range of its silicon network (between 0.44-0.83 nm), while the kinetic diameter of the acetic acid molecule is 0.43 nm. In the process of pervaporation separation of acetic acid dehydration, the pore size screening effect is weak, resulting in a low acetic acid / water separation factor (Journal of Membrane Science 421-422 (2012) 25-31; Journal of Membrane Science 428 (2013) 157-162). Chinese patent CN106823850B uses the hydrochloric acid vapor method, which reduces the membrane pore size but leads to a decrease in its water flux. On the other hand, the silica sol prepared by the hydrolysis-polymerization method often has a bimodal distribution of particle size, which affects the formation of the sub-nanometer pore size of the membrane.

[0004] Two-dimensional materials such as graphene and carbon nitride can be prepared into membranes and separated by periodic defect holes or lamellar channels. However, their mechanical strength is low and their performance in molecular separation is limited. For example, Chinese patent CN113578072A discloses that carbon nitride membranes can be used for Mg 2+The hydrated ions (0.8nm) of the organic film have a certain separation effect, but are limited in the separation of small molecules such as acetic acid / water. Doping two-dimensional materials into organic membranes to prepare hybrid membranes is an effective way to separate molecules. Patent (CN106268332) discloses that the addition of graphite phase C3N4 to polyvinyl alcohol improves the performance of pervaporation separation of ethanol and water. Therefore, the preparation of organosilicon blended membranes doped with two-dimensional materials is expected to improve the pervaporation separation performance. However, due to the uneven particle size of the synthesized organosilicon sol, and the two-dimensional nanosheets are easy to agglomerate to form uneven-sized sheets, defects are prone to occur after blending, affecting the separation performance of the membrane. Summary of the invention

[0005] Purpose of the invention: In view of the shortcomings of the prior art, a method for preparing a blended membrane by uniformly regulating two-dimensional material-organosilicon is provided, wherein the organosilicon sol and the two-dimensional lamellar sol are preferentially filtered through microfiltration membranes with two pore sizes to improve their uniformity, and then the two-dimensional material is ultrasonically intercalated into the organosilicon sol. Through the complementarity of the two materials, the pore size of the silicon network is effectively reduced, and the hydrophilic groups of the two-dimensional material are utilized for the dehydration separation of the pervaporation acetic acid / water solution to improve the separation factor and water permeation flux.

[0006] Technical solution: The purpose of the present invention is achieved through the following technical solution:

[0007] The present invention provides a method for uniformly regulating and preparing a blended film of a two-dimensional material and organic silicon, comprising the following steps:

[0008] (1) dissolving an organic alkoxysilane in a solvent, adding a catalyst and water, performing a hydrolysis polymerization reaction to obtain an organic silicon sol, and filtering the organic silicon sol through a microfiltration membrane;

[0009] (2) preparing a two-dimensional sheet material by an exfoliation method, dispersing it in an ethanol-water solution to obtain a two-dimensional sheet solution, and filtering it through a microfiltration membrane;

[0010] (3) ultrasonically mixing the organosilicon sol of step (1) and the two-dimensional lamellar sol of step (2) to obtain a mixed sol, and further diluting it with a solvent;

[0011] (4) Applying the mixed sol of step (3) on a porous carrier and calcining at high temperature to obtain a two-dimensional material-organic silicon blend membrane.

[0012] Preferably, in step (1), the organic alkoxysilane is one or more of bis(triethoxysilyl)methane, 1,2-bis(triethoxysilyl)ethane or 1,3-bis(triethoxysilyl)propane; and the catalyst is one or more of hydrochloric acid, nitric acid or sulfuric acid.

[0013] Preferably, in step (1), the molar ratio of the organic alkoxysilane, water and catalyst is 1:60-150:0.1-0.8; and the mass fraction of the organic alkoxysilane in the mixed solution is 2.0-6.0 wt%.

[0014] Preferably, in step (1), the hydrolysis polymerization reaction temperature is 30 to 50° C., and the hydrolysis polymerization reaction time is 2 to 6 hours.

[0015] Preferably, in step (2), the two-dimensional sheet material is graphene, carbon nitride or molybdenum sulfide.

[0016] More preferred is graphite-like carbon nitride (g-C3N4) containing hydrophilic groups. g-C3N4 containing amino groups is ultrasonically intercalated into the organosilicon network to form a small size that can effectively screen acetic acid, and the amino groups can effectively increase its hydrophilicity.

[0017] The preparation method of the two-dimensional sheet material is as follows: melamine is heated at 550° C. in air for 4 hours to prepare bulk g-C3N4, and then the bulk carbon nitride is ball-milled for 10 minutes, and then dispersed in a 25wt% ethanol aqueous solution for ultrasonic mechanical exfoliation, and finally centrifuged, the supernatant is filtered and dried to obtain a nanosheet.

[0018] Preferably, in step (2), the concentration of the two-dimensional sheet material in the ethanol-water solution is 1 to 5 mg / ml.

[0019] Preferably, in step (1), the organosilicon sol is filtered under pressure through an organic filter membrane of 0.1 to 0.22 μm to obtain sol particles with a uniform particle size of about 1 to 2 nm; in step (2), the two-dimensional sheet sol solution is filtered under pressure through an organic filter membrane of 0.45 to 1.0 μm to obtain small sheets with a uniform particle size of less than 400 nm. The membrane material of the microfiltration membrane is a polytetrafluoroethylene filter membrane or an organic nylon filter membrane.

[0020] Furthermore, the solution is filtered through the membrane using a syringe filter press.

[0021] Preferably, in step (3), the mass ratio of the organosilicon to the two-dimensional sheet material in the mixed sol is 1:0.01-0.14; and the concentration of the organosilicon in the mixed sol after further dilution is 0.5-1.5 wt %.

[0022] Furthermore, the filtered two-dimensional sheet solution and the organic silica sol were simultaneously sonicated for 1 hour, and the two were mixed and then sonicated for another 1 to 2 hours.

[0023] Preferably, in step (4), the high temperature calcination is carried out at a temperature of 200 to 300° C. for a time of 20 to 80 minutes, and the rubbing and calcination steps are repeated 2 to 4 times.

[0024] The present invention also provides the application of the method for preparing a blended membrane by uniformly regulating the two-dimensional material-organic silicon in dehydration separation of an acidic solution by pervaporation.

[0025] Beneficial effects of the present invention:

[0026] The present invention prepares a defect-free two-dimensional lamellar / organosilicon blended membrane by pre-filtering an organosilicon sol and a two-dimensional lamellar sol solution through microfiltration membranes with two pore sizes to obtain a uniform mixed sol. The two materials complement each other to effectively reduce the pore size of the silicon network, and utilize the hydrophilic groups of the two-dimensional material to improve the separation factor and water permeation flux in the dehydration separation of pervaporation acetic acid / water solution. On the one hand, the two-dimensional material contains hydrophilic groups, which makes the organosilicon membrane more hydrophilic and has a larger water flux in the separation process. On the other hand, the interlayer spacing of the two-dimensional material is smaller than that of acetic acid molecules, but larger than that of water molecules, and has stronger water selectivity in the acetic acid dehydration separation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the TEM image of the two-dimensional material in Example 1.

[0028] Figure 2 This is the SEM image of the pure BTESE membrane prepared in Comparative Example 1.

[0029] Figure 3 The water contact angle of the blended films formed by adding different proportions of g-C3N4 into BTESE. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is described in detail below through specific embodiments, but the protection scope of the present invention is not limited to the embodiments.

[0031] Example 1

[0032] 15.9 g of ethanol, 1.0 g of 1,2-bis(triethoxysilyl)ethane BTESE and 3.0 g of water were added to a beaker in sequence, and then 0.1 g of 35 wt.% HCl was added to form a uniform 5 wt% BTESE solution, which was stirred in a 40°C water bath for 3 h to prepare a BTESE sol. The solution was drawn up with a syringe and filtered through a 0.1 μm polytetrafluoroethylene filter membrane.

[0033] Melamine was heated at 550 °C in air for 4 h to prepare bulk g-C3N4, and then the bulk carbon nitride was ball-milled for 10 min, dispersed in a 25 wt% ethanol aqueous solution for ultrasonic mechanical exfoliation, and finally centrifuged, the supernatant was filtered and dried to obtain nanosheets (from Figure 1It can be seen that it is a two-dimensional structure). 4 ml of anhydrous ethanol was added to 6 ml of deionized water, and then 10 mg of nanosheets were added thereto. After ultrasonic dispersion, a 1 mg / ml g-C3N4 sol solution was obtained, and then the sol solution was sucked with a syringe and filtered through a 0.45 μm polytetrafluoroethylene filter membrane.

[0034] Take 1.0ml of the filtrate and 1g of the filtered BTESE sol, add a certain amount of ethanol to 10g, and after ultrasonic treatment for 1h, a uniformly dispersed g-C3N4 / BTESE mixed sol is obtained. The obtained organic silicon concentration is 0.5wt%. It is rubbed on a ceramic tube and calcined at 250℃ for 20min. Repeat 3 times.

[0035] The feed liquid is a 90wt% acetic acid aqueous solution through the blended membrane for pervaporation test (GB / T34243-2017). At a temperature of 75°C, the separation performance obtained is: the flux is 1.75kg·m -2 ·h -1 , the separation factor is 1600.

[0036] Example 2

[0037] The process of preparing the blended membrane is basically the same as that in Example 1, except that 3.0 ml of the g-C3N4 filtrate and 1 g of the filtered BTESE sol are taken, and finally a certain amount of ethanol is added to 10 g, and then ultrasonicated for 2 h to obtain a uniformly dispersed g-C3N4 / BTESE mixed sol.

[0038] The feed liquid was a 90wt% acetic acid aqueous solution and passed through the blended membrane for pervaporation test (GB / T34243-2017). At a temperature of 75°C, the separation performance was: the flux was 2.2kg·m -2 ·h -1 , the separation factor is 3300.

[0039] Example 3

[0040] The process of preparing the blended membrane is basically the same as that in Example 1, except that 5.0 ml of g-C3N4 filtrate and 1 g of filtered BTESE sol are taken, and finally a certain amount of ethanol is added to 10 g, and then ultrasonicated for 2 h to obtain a uniformly dispersed g-C3N4 / BTESE mixed sol.

[0041] The feed liquid is a 90wt% acetic acid aqueous solution through the blended membrane for pervaporation test (GB / T34243-2017). At a temperature of 75°C, the separation performance obtained is: the flux is 2.3kg·m -2 ·h -1 , the separation factor is 1400.

[0042] Example 4

[0043] The process of preparing the blended membrane is basically the same as that in Example 1, except that 7.0 ml of the g-C3N4 filtrate and 1 g of the filtered BTESE sol are taken, and finally a certain amount of ethanol is added to 10 g, and then ultrasonicated for 2 h to obtain a uniformly dispersed g-C3N4 / BTESE mixed sol.

[0044] The feed liquid is a 90wt% acetic acid aqueous solution and is subjected to a pervaporation test (GB / T34243-2017) through a blended membrane. At a temperature of 75°C, the separation performance obtained is: the flux is 2.5kg·m -2 ·h -1 , the separation factor is 600.

[0045] From Examples 1-4, it can be seen that as the amount of two-dimensional material added increases, the separation factor of the blended membrane is improved, but when the amount of two-dimensional material increases to a certain extent, continuing to add too many two-dimensional sheets will lead to a decrease in the separation factor of the blended membrane. This is because excessive two-dimensional sheets agglomerate into large particles, affecting the integrity of the BTESE network.

[0046] Example 5

[0047] 32.8 g of ethanol, 1.0 g of 1,2-bis(triethoxysilyl)ethane BTESE and 6.0 g of water were added to a beaker in sequence, and then 0.2 g of 35 wt.% HCl was added to form a 2.5 wt% BTESE solution, which was then placed in a 40°C water bath and stirred for 4 h to prepare a BTESE sol. The solution was drawn up with a syringe and filtered through a 0.1 μm polytetrafluoroethylene filter membrane.

[0048] Melamine was heated at 550°C in air for 4 hours to prepare bulk g-C3N4, and then the bulk carbon nitride was ball-milled for 10 minutes, and then dispersed in a 25wt% ethanol aqueous solution for ultrasonic mechanical exfoliation, and finally centrifuged, and the supernatant was filtered and dried to obtain nanosheets. 4ml of anhydrous ethanol was added to 6ml of deionized water, and then 20mg of nanosheets were added thereto, and a 2mg / ml g-C3N4 dispersion was obtained by ultrasonic dispersion, and then the solution was drawn with a syringe and filtered through a 0.45μm polytetrafluoroethylene filter.

[0049] Take 1.0 ml of the filtrate and 2 g of the filtered BTESE sol, add a certain amount of ethanol to 5 g, and after ultrasonic treatment for 2 hours, a uniformly dispersed g-C3N4 / BTESE mixed sol with a silicone concentration of 1 wt% was obtained. Apply it on a ceramic tube and calcine at 250°C for 20 min, and repeat twice.

[0050] The feed liquid is a 90wt% acetic acid aqueous solution through the blended membrane for pervaporation test (GB / T34243-2017). At a temperature of 75°C, the separation performance obtained is: the flux is 1.1kg·m -2 ·h -1 , the separation factor is 2000.

[0051] Example 6

[0052] 15.9 g of ethanol, 1.0 g of 1,2-bis(triethoxysilyl)ethane BTESE and 3.0 g of water were added to a beaker, and then 0.1 g of 35 wt.% HCl was added to form a uniform 5 wt.% BTESE solution, which was then stirred in a 40°C water bath for 3 h to prepare a BTESE sol. The solution was drawn up with a syringe and filtered through a 0.22 μm polytetrafluoroethylene filter membrane.

[0053] Melamine was heated at 550°C in air for 4 hours to prepare bulk g-C3N4, and then the bulk carbon nitride was ball-milled for 10 minutes, and then dispersed in a 25wt% ethanol aqueous solution for ultrasonic mechanical exfoliation, and finally centrifuged, and the supernatant was filtered and dried to obtain nanosheets. 4ml of anhydrous ethanol was added to 6ml of deionized water, and then 10mg of nanosheets were added thereto, and a 1mg / ml dispersion was obtained by ultrasonic dispersion, and then the solution was drawn with a syringe and filtered through a 0.8μm organic nylon filter membrane.

[0054] Take 1.0ml of the filtrate and 1g of BTESE sol, add a certain amount of ethanol to 10g, and after ultrasonic treatment for 2h, a uniformly dispersed g-C3N4 / BTESE mixed sol with a silicone concentration of 0.5wt% was obtained. Then it was rubbed on a ceramic tube and calcined at 250℃ for 20min, and repeated 3 times.

[0055] The feed liquid is a 90wt% acetic acid aqueous solution and is subjected to a pervaporation test (GB / T34243-2017) through a blended membrane. At a temperature of 75°C, the separation performance obtained is: the flux is 2.5kg·m -2 ·h -1 , the separation factor is 1100.

[0056] Example 7

[0057] 15.9 g of ethanol, 1.0 g of 1,2-bis(triethoxysilyl)ethane BTESE and 3.0 g of water were added to a beaker in sequence, and then 0.1 g of 35 wt.% HCl was added to form a uniform 5 wt% BTESE solution, which was then stirred in a 40°C water bath for 3 h to prepare a BTESE sol. The solution was drawn up with a syringe and filtered through a 0.1 μm polytetrafluoroethylene filter membrane.

[0058] 4 ml of anhydrous ethanol was added to 6 ml of deionized water, and then 20 mg of graphene nanosheets were added thereto. After ultrasonic dispersion, a 2 mg / ml graphene dispersion was obtained. The solution was then drawn up with a syringe and filtered through a 0.8 μm polytetrafluoroethylene filter membrane.

[0059] Take 1.0 ml of graphene filtrate and 1 g of filtered BTESE sol, add a certain amount of ethanol to 10 g, and after ultrasonic treatment for 2 hours, a uniformly dispersed graphene / BTESE mixed sol with an organosilicon sol concentration of 0.5 wt% is obtained. Then, it is rubbed on a ceramic tube and calcined at 250°C for 20 min, and repeated 3 times.

[0060] The feed liquid is a 90wt% acetic acid aqueous solution and is subjected to pervaporation test (GB / T34243-2017) through the blended membrane. At a temperature of 75°C, the separation performance obtained is: the flux is 0.8kg·m -2 ·h -1 , the separation factor is 1490.

[0061] The two-dimensional material of this embodiment is graphene. Since graphene does not contain hydrophilic groups, the flux growth of the blended membrane is limited compared with carbon nitride, but it has a screening function, so the separation factor of the blended membrane of this embodiment is increased.

[0062] Comparative Example 1

[0063] 15.9g of ethanol, 1.0g of BTESE and 3.0g of water were added to a beaker in sequence, and then 0.1g of HCl with a mass fraction of 35wt.% was added to form a uniform 5wt.% BTESE solution, which was then placed in a 40°C water bath and stirred for 3h to prepare a BTESE sol. The prepared BTESE sol was filtered with a 0.1μm polytetrafluoroethylene filter membrane, applied on a support and calcined, with a calcination time of 20min and a calcination temperature of 250°C, and was applied and calcined 3 times in total. Figure 2 This is the SEM image of the prepared BTESE membrane. It can be seen from the image that the surface of the prepared BTESE membrane is smooth and continuous.

[0064] The feed liquid was a 90wt% acetic acid aqueous solution and passed through an organic silicon membrane for pervaporation test (GB / T34243-2017). At a temperature of 75°C, the separation performance was: the flux was 1.3kg·m -2 ·h -1 , the separation factor is 550.

[0065] Comparative Example 2

[0066] 15.9 g of ethanol, 1.0 g of 1,2-bis(triethoxysilyl)ethane BTESE and 3.0 g of water were added to a beaker in sequence, and then 0.1 g of 35 wt.% HCl was added to form a uniform 5 wt% BTESE solution, which was then placed in a 40°C water bath and stirred for 3 h to prepare a BTESE sol.

[0067] Melamine was heated at 550 °C in air for 4 h to prepare bulk g-C3N4, and then the bulk carbon nitride was ball-milled for 10 min, dispersed in a 25 wt% ethanol aqueous solution for ultrasonic mechanical exfoliation, and finally centrifuged, the supernatant was filtered and dried to obtain nanosheets (from Figure 1 It can be seen that it is a two-dimensional structure). 4 ml of anhydrous ethanol was added to 6 ml of deionized water, and then 10 mg of nanosheets were added thereto, and 1 mg / ml of g-C3N4 sol solution was obtained by ultrasonic dispersion.

[0068] Take 1.0ml of the filtrate and 1g of the filtered BTESE sol, add a certain amount of ethanol to 10g, and after ultrasonic treatment for 2h, a uniformly dispersed g-C3N4 / BTESE mixed sol is obtained. The obtained organic silicon concentration is 0.5wt%. It is rubbed on a ceramic tube and calcined at 250℃ for 20min. Repeat 3 times.

[0069] The feed liquid is a 90wt% acetic acid aqueous solution and is subjected to pervaporation test (GB / T34243-2017) through the blended membrane. At a temperature of 75°C, the separation performance obtained is: the flux is 1.6kg·m -2 ·h -1 , the separation factor is 960.

[0070] Figure 3 This is a summary diagram of the water contact angles of the membranes prepared in Examples 1-4 and Comparative Example 1. It can be seen that as the doping amount of g-C3N4 increases, the hydrophilicity of the membrane also increases, which is beneficial to the preferential adsorption of water by the membrane during the separation process, thereby improving the separation water flux.

[0071] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention as defined in the appended claims.

Claims

1. A method for preparing a pervaporation blend membrane by uniformly regulating a two-dimensional material and silicone, characterized in that: The following steps are involved: (1) dissolving the organoalkoxysilane in a solvent, adding a catalyst and water, undergoing a hydrolysis polymerization reaction to obtain an organosilica sol, and filtering the sol through a microfiltration membrane; (2) preparing a two-dimensional sheet material by an exfoliation method, dispersing it in an ethanol-water solution to obtain a two-dimensional sheet sol solution, and filtering it through a microfiltration membrane; (3) ultrasonically mixing the organosilicon sol of step (1) and the two-dimensional lamellar sol of step (2) to obtain a mixed sol, and further diluting it with a solvent; (4) applying the mixed sol of step (3) onto a porous carrier and calcining at high temperature to obtain a two-dimensional material-organic silicon blend membrane; In step (1), the organosilicon sol is filtered under pressure through an organic filter membrane of 0.1-0.22 μm to obtain sol particles with a uniform particle size of 1-2 nm; In step (2), the two-dimensional sheet sol solution is filtered under pressure through a 0.45-1.0 μm organic filter membrane to obtain small sheets with a uniform particle size of less than 400 nm; The mass ratio of the organosilicon to the two-dimensional sheet material in the mixed sol is 1:0.01-0.14; The two-dimensional sheet material is a graphite-like carbon nitride g-C3N4 containing a hydrophilic group.

2. The method for preparing a pervaporation blend membrane by uniformly regulating a two-dimensional material and organic silicon according to claim 1, characterized in that: In step (1), the organic alkoxysilane is one or more of bis(triethoxysilyl)methane, 1,2-bis(triethoxysilyl)ethane or 1,3-bis(triethoxysilyl)propane; and the catalyst is one or more of hydrochloric acid, nitric acid or sulfuric acid.

3. The method for preparing a pervaporation blend membrane by uniformly regulating a two-dimensional material and silicone according to claim 1, characterized in that: In step (1), the molar ratio of the organic alkoxysilane, water and catalyst is 1: 60-150: 0.1-0.8; the mass fraction of the organic alkoxysilane in the mixed solution is 2.0-6.0 wt%.

4. The method for preparing a pervaporation blend membrane by uniformly regulating a two-dimensional material and organic silicon according to claim 1, characterized in that: In step (1), the hydrolysis polymerization reaction temperature is 30 to 50° C., and the hydrolysis polymerization reaction time is 2 to 6 hours.

5. The method for preparing a pervaporation blend membrane by uniformly regulating a two-dimensional material and organic silicon according to claim 1, characterized in that: In step (2), the concentration of the two-dimensional sheet material in the ethanol-water solution is 1-5 mg / ml.

6. The method for preparing a pervaporation blend membrane by uniformly regulating a two-dimensional material and silicone according to claim 1, characterized in that: The membrane material of the microfiltration membrane is a polytetrafluoroethylene filter membrane or an organic nylon filter membrane.

7. The method for preparing a pervaporation blend membrane by uniformly regulating a two-dimensional material and organic silicon according to claim 1, characterized in that: In step (3), the concentration of the organic silicon in the mixed sol is 0.5 to 1.5 wt %.

8. The method for preparing a pervaporation blend membrane by uniformly regulating a two-dimensional material and organic silicon according to claim 1, characterized in that: In step (4), the high temperature calcination temperature is 200-300°C, the time is 20-80 minutes, and the rubbing and calcination steps are repeated 2-4 times.

9. A blended membrane obtained by the method for preparing a pervaporation blended membrane by uniformly regulating a two-dimensional material and organic silicon as described in any one of claims 1 to 8.

10. Use of the blended membrane according to claim 9 in dehydration separation of an acidic solution by pervaporation.

Citation Information

Patent Citations

  • A method for controlling the pore size of a bridge-type silicone membrane

    CN106823850B

  • Preparation method and application of compact graphite phase carbon nitride film

    CN113578072A

  • MoS2 / organic silicon blended matrix membrane, preparation method and application thereof

    CN113856489A